Comparison of Post-Operative Pain Score Between Open Appendectomy and Laparoscopic Appendectomy on Acute Appendicitis Patient in Siloam Hospital Lippo Village - Elsa, Mary Christina; Sudirman, Taufik (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Appendicitis is inflammation of vermiform appendix which can be caused by luminal obstruction. Appendicitis is one of the most common causes of emergency abdominal surgery, with 11 cases per 10.000 person per year. Until today, open appendectomy is still the gold standard for appendicitis treatment although laparoscopic appendectomy has significantly lower post-operative pain.Methods: This study uses cross-sectional study design with post-open appendectomy and laparoscopic appendectomy patients in Siloam Hospital Lippo Village as the sample population. The Visual Analogue Scale (VAS) is taken from patient’s medical record and processed using Mann-U-Whitney test.Result: From 70 acute appendicitis patients, 36 underwent open appendectomy and 34 underwent laparoscopic appendectomy. The result showed the median score of VAS 1 day post open appendectomy surgery (median = 3, min/max = 2/6 [95% CI = 2,55 – 3,14]) is higher than post laparoscopic appendectomy (median = 2,25, min/max = 0/4, [95% CI = 1,97 – 2,59]), with adjusted p value against age and surgery duration is 0,024. In pediatric patients, median score of VAS 1 day post open appendectomy surgery is the same with laparoscopic appendectomy (median = 3, p value = 0,863). Multivariate analysis showed that surgery duration affects VAS 1 day post appendectomy surgery in pediatric patients (p value = 0,042).Conclusions: This study shows that the median score of VAS 1 day post open appendectomy surgery is higher than laparoscopic appendectomy. This result is statistically significant. However, in pediatric patients the median score of VAS 1 day post open appendectomy surgery and laparoscopic appendectomy is the same. VAS 1 day post appendectomy surgery in pediatric patients is affected by surgery duration.